Does Germany collect revenue from taxing capital income? - Johannes Becker; Clemens Fuest (Center for Economic Studies and ifo Institute (CESifo), 2005)
A widespread objection to the introduction of consumption tax systems claims that this would lead to high tax revenue losses. This paper investigates the revenue effects of a consumption tax reform in Germany. Our results suggest that the revenue losses would be surprisingly low. We find a maximum revenue loss of 1.6 percent of annual GDP. In some years, we even find a tax revenue gain. This implies that the current tax system collects little revenue from taxing the normal return to capital. Based on these results, we calculate a macroeconomic measure of the effective tax rate on capital income.
Keywords: H21; H25; 330; cash flow tax; tax revenue effects; effective taxation of capital income; Kapitalertragsteuer; Steueraufkommen; Ausgabensteuer; Steuerreform; Deutschland